Enhancing Virtual Machine Live Migration Time Using Vcpu Limits - Abdel Latief Dewan, Aula; Abood Ahmed, Rabah (International Journal of Engineering and Technology, 2018)
In the Cloud Computing, the live migration of a virtual machine or VM from one physical machine to another is a vital process applied on the service provider side. Live migration helps administrators manage data centers resources optimally. Due to the intensive daily use, it is necessary to improve the performance of VM migration-this is reflected in improving the quality of service provided to the customer while minimizing the costs incurred. Pre-copy is an important method of live migration that has been adopted in many cloud computing platforms. One main drawback of this method is the degradation of its performance when the migrating VM runs one or more of the processes that write on the memory pages faster than the speed of transferring those pages. This makes migration time-consuming. In this paper, we propose an approach to address this issue by reducing the generation rate of the modified pages while maintaining the service provided to the customer. This approach was applied to the real Xen platform and the results showed an improvement in the time of live migration of the virtual machine that runs an intensive write process up to 40% compared to the migration time of the original Xen platform.
Keywords: virtual machine; live migration; pre-copy method; virtualization; cpulimit; cloud computing.